Peningkatan Penalaran Dan Hasil Belajar Matematika Melalui Cooperative Learning Tipe Inside Outside Circle Pada Siswa Kelas VII B Semester Ganjil SMP N 3 Boyolali Tahun Ajaran 2015/2016 - SETYANINGSIH, AFIAH (2016)
The purpose of this research is to increase of reasoning and final results mathematics students of class VII B SMP N 3 Boyolali through Cooperative Learning Type Inside Outside Circle. This is a classroom action research. Data collection methods used were interviews, observation, field notes, documentation, and a written test. Data analysis techniques used are data reduction, data presentation, and conclusion. The results of the research showed an increased ability of reasoning can be seen from 1) students filed allegations of (28.125%) increased to (75%), 2) the students compile evidence, giving reasons or evidence of the correctness of the solution (31.25%) increased to (81.25%), 3) the students make a conclusions from the statements of (31.25%) increased to (78.125%). An increase mathematics final result can be seen from the students who received grades of more than equal to Kriteria Ketuntasan Minimal (KKM) of (43.75%) increased to (81.25%). Based on this research, concluded that the application of Cooperative Learning Type Inside Outside Circle in mathematics learning can be increase of reasoning and mathematics final result.